2022
DOI: 10.3389/fmicb.2022.1064904
|View full text |Cite
|
Sign up to set email alerts
|

The devil is in the details: Variable impacts of season, BMI, sampling site temperature, and presence of insects on the post-mortem microbiome

Abstract: BackgroundPost-mortem microbial communities are increasingly investigated as proxy evidence for a variety of factors of interest in forensic science. The reported predictive power of the microbial community to determine aspects of the individual’s post-mortem history (e.g., the post-mortem interval) varies substantially among published research. This observed variation is partially driven by the local environment or the individual themselves. In the current study, we investigated the impact of BMI, sex, insect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…sex, body mass and disease state at time of death). Indeed, while temperature is a major extrinsic environmental factor that significantly impacts decomposition rates, it is also suggested that intrinsic factors may impact microbial activity and lead to inter-individual variability in decomposition patterns [ 47 , 48 ]. Hence, the current dataset was divided according to the intrinsic factors sex (female and male) and body mass (slim and medium/large) and the subsets discussed individually.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…sex, body mass and disease state at time of death). Indeed, while temperature is a major extrinsic environmental factor that significantly impacts decomposition rates, it is also suggested that intrinsic factors may impact microbial activity and lead to inter-individual variability in decomposition patterns [ 47 , 48 ]. Hence, the current dataset was divided according to the intrinsic factors sex (female and male) and body mass (slim and medium/large) and the subsets discussed individually.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, no peptide ratio could be found for the subgroup “body mass medium/large” that satisfied all defined filter criteria (see material and methods section). The BMI was previously highlighted as a potential intrinsic factor for inter-individual differences in the postmortem microbiome and decomposition patterns [ 47 , 48 ]. It was therefore surprising to not be able to identify more body mass-specific peptide ratios within the current dataset.…”
Section: Resultsmentioning
confidence: 99%
“…Carcass mass and body mass index are poorly understood variables associated with apparently contrasting experimental results [ 31 , 78 , 82 , 83 ]. Mason et al [ 84 ] and Tarone et al [ 85 ] observed relationships between human body mass index and microbial diversity while Dawson et al (2021) observed little effect of carcass mass on insect communities. Insects are clearly a primary decomposer group in the tropics and it would be informative to know if there exists a threshold carcass mass below which there is a significant difference in decomposer community structure [ 78 , [85] , [86] , [87] ].…”
Section: Discussionmentioning
confidence: 99%
“…Mason et al [ 84 ] and Tarone et al [ 85 ] observed relationships between human body mass index and microbial diversity while Dawson et al (2021) observed little effect of carcass mass on insect communities. Insects are clearly a primary decomposer group in the tropics and it would be informative to know if there exists a threshold carcass mass below which there is a significant difference in decomposer community structure [ 78 , [85] , [86] , [87] ]. A mass threshold might indicate a different series of decomposition processes for smaller carcasses that affects the heterogeneity of the CDI by providing insufficient area for the formation of larval masses.…”
Section: Discussionmentioning
confidence: 99%
“…Such insects change the microbiome through their secretions and excretions, including symbiotic microbes and microbial and immune products. One study showed that the presence of bacteria of the genus Ignatzschineria marks the presence of insects [44].…”
Section: Patterns Of Microbial Dynamics After Deathmentioning
confidence: 99%